When all light fails - Silvis, Randall, 1950- (Ryan DeMarco mystery, 2021)
"There's not much that would convince retired police sergeant Ryan DeMarco to take on another private investigation case, but he can't refuse a nine-year-old girl begging for help finding her biological father. DeMarco and his partner, Jayme, get some good leads, but then tragedy strikes. The girl and her grandmother are found dead in their home, supposedly of carbon monoxide poisoning from a blocked furnace vent. But something feels fishy to DeMarco, and he keeps digging. What he finds is rampant corruption, from a local judge to the fire inspector. In When All Light Fails, the secrets DeMarco digs up are darker than anyone could have imagined"--